Relationship between match playing performance and muscular strength and power in professional rugby league - Redman, K.; Wade, L.; Whitley, R.; Connick, M.; Kelly, V. G.; Beckman, E. (Journal of Australian Strength and Conditioning, 2019)
Identifying the strength and power characteristics that are related to positive match playing performance during rugby league match play will allow physical performance staff to focus on developing these attributes during resistance training sessions.